Perceptual responses in patients with inflammatory and functional bowel disease. Issue 4 (1st October 2000) - Chang, L; Munakata, J; Mayer, E A; Schmulson, M J; Johnson, T D; Bernstein, C N; Saba, L; Naliboff, B; Anton, P A; Matin, K
Abstract : BACKGROUND AND AIMS: Enhanced visceral sensitivity following a transient inflammatory process in the gut has been postulated as an aetiological mechanism of irritable bowel syndrome (IBS). In this study we compared perceptual responses to rectosigmoid distension in patients with mild chronic inflammation of the rectum (ulcerative colitis (UC)) and patients without mucosal inflammation (IBS) to determine if chronic low grade mucosal inflammation may be a plausible explanation for rectosigmoid hypersensitivity reported in both IBS and UC patients. METHODS: UC disease activity was quantified using activity index scores. Perception thresholds for discomfort during rectosigmoid distension were compared between 11 UC patients with quiescent or mild disease activity, 18 IBS patients, and 13 healthy controls. RESULTS: Although UC activity index scores negatively correlated with perceptual thresholds for discomfort ( r =−0.76, p=0.016), UC patients had higher discomfort thresholds compared with IBS patients and controls before (p=0.02) and after (p < 0.001) a noxious sigmoid conditioning stimulus. CONCLUSIONS: Rectal perception was attenuated in UC but enhanced in IBS. In chronic mild inflammation, activation of antinociceptive mechanisms may prevent the development of visceral hyperalgesia. Low grade mucosal inflammation alone is unlikely to be responsible for symptoms in functional gastrointestinal disorders.